Assessment model for the justification of intrusive lifestyle interventions: literature study, reasoning and empirical testing. - Wesseling, Michiel; Wigersma, Lode; van der Wal, Gerrit (BMC Medical Ethics, 2016)
Background: In many countries health insurers, employers and especially governments are increasingly using pressure and coercion to enhance healthier lifestyles. For example by ever higher taxes on cigarettes and alcoholic beverages, and ever stricter smoke-free policies. Such interventions can enhance healthier behaviour, but when they become too intrusive, an unfree society can emerge. Which lifestyle interventions that use pressure or coercion are justifiable and which are not? We tried to develop an assessment model that can be used for answering this question, on a generally acceptable way, for all sorts of lifestyle interventions.Methods: The intended assessment model was developed in three phases. In the first phase the model was theoretically developed on the basis of literature study and reasoning. In the second phase the model was empirically tested by assessing two detailed cases from everyday practice using the model. The model was improved again and again. In the third phase (publication phase) the 10(th) version of the model was developed while writing this article.Results: An assessment model for the justification of intrusive lifestyle interventions. It comprises three components: (1) 12 assessment criteria (necessity, causality, responsibility, appropriate design, effectiveness, intrusiveness, burdens-benefits-ratio, fairness, support, complementary policies, verifiability, implementation capacity); (2) an assessment structure with three filters (design logic, effects and side effects, implementation); (3) a way of assessing (based on reasonableness and transparency).Conclusions: We have developed an assessment model for the justification of lifestyle interventions that use pressure or coercion to promote health. The correctness, completeness and practicality of the model are likely. Important principles for the justification are the logic and completeness of the underlying argumentation and the proper use of the available scientific information. Parties for and against a particular intervention could use the model to test and strengthen their argumentation and to improve the quality of the intervention.